Correlation analysis of larger side bone cement volume/vertebral body volume ratio with adjacent vertebral compression fractures during vertebroplasty - Zhou, Chengqiang; Huang, Shaolong; Liao, Yifeng; Chen, Han; Zhang, Yazhong; Li, Hua; Zhu, Ziqiang; Wang, Yunqing (Frontiers in Endocrinology, 2023)
Objective: To investigate the correlation analysis of larger side bone cement volume/vertebral body volume ratio (LSBCV/VBV%) with adjacent vertebral compression fracture (AVCF) in percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fracture (OVCF). Methods: A retrospective analysis of 245 OVCF patients who underwent PVP treatment from February 2017 to February 2021, including 85 males and 160 females. The age ranged from 60 to 92 years, with a mean of (70.72±7.03) years. According to whether AVCF occurred after surgery, they were divided into 38 cases in the AVCF group (fracture group) and 207 cases in the no AVCF group (non-fracture group). The correlation between gender, age, bone mineral density (BMD), body mass index (BMI), thoracolumbar segment fracture, bone cement disc leakage, LSBCV, bone cement volume (BCV), VBV, LSBCV/VBV ratio (LSBCV/VBV%), and BCV/VBV% and AVCF were analyzed in both groups. Risk factors for AVCF after PVP were analyzed by multifactorial logistic regression, and then the receiver operating characteristic curves (ROC curves) were plotted to identify the critical value of LSBCV/VBV%. Results: 38 patients (15.5%) developed AVCF postoperatively. Univariate analysis showed that BMD, bone cement disc leakage, LSBCV, and LSBCV/VBV% were risk factors for AVCF after PVP, while gender, age, BMI, thoracolumbar segment fracture, BCV, VBV, and BCV/VBV% were not significantly different in both groups (P>0.05). Multifactorial logistic regression analysis revealed that BMD, cement disc leakage, and LSBCV/VBV% were independent risk factors for AVCF after PVP (P<0.05). According to the ROC curve, the LSBCV/VBV% had an area under the curve of 71.6%, a sensitivity and specificity of 89.5% and 51.7%, respectively, and a critical value of 13.82%. Conclusions: BMD, bone cement disc leakage and LSBCV/VBV% are independent risk factors for AVCF after PVP. With LSBCV/VBV at 13.82%, the incidence of AVCF significantly increased.